Narrowband Emission from Organic Fluorescent Emitters with Dominant Low‐Frequency Vibronic Coupling. Issue 4 (16th December 2020) - Qiu, Xu; Tian, Guangjun; Lin, Chengwei; Pan, Yuyu; Ye, Xiyun; Wang, Bohan; Ma, Dongge; Hu, Dehua; Luo, Yi; Ma, Yuguang
Abstract: Organic fluorescent emitters with narrowband emissions are highly desirable for high‐resolution organic light‐emitting diode (OLED) display technology. In principle, this can be achieved by specifically controlling the intrinsic structural relaxation and vibronic coupling in the excited state. Here, a design strategy to realize narrowband emission of organic fluorescent emitters is proposed by significantly enhancing the low‐frequency vibronic coupling strength ( Λ ) while simultaneously reducing the high‐frequency Λ of the commonly involved stretching modes. The quinolino‐[3, 2, 1‐ de ]acridine‐5, 9‐dione (QAO) species is found to be directly associated with this design principle. By introducing single bond‐linked peripheral moieties into the QAO core, the constructed QAO derivatives are shown to exhibit better performance, by achieving a full width at half‐maximum of 23 nm/0.13 eV in toluene for the narrowest band as well as 27 nm/0.15 eV in doped devices, with negligible dependence on the doping concentrations. The maximum external quantum efficiency of the fabricated blue OLED is 17.5%. Abstract : A design strategy to realize narrowband emission of organic fluorescent emitters by significantly enhancing the low‐frequency vibronic coupling strength ( Λ ) while simultaneously reducing the high‐frequency Λ of the commonly involved stretching modes is proposed. The emitters achieve a full width at half‐maximum of 23 nm/0.13 eV in toluene for the narrowest band and 27 nm/0.15 eV in doped devices.